Islamization of Knowledge: Theoretical Foundations, Contexts, and Contemporary Debates on Ismail Raji al-Faruqi’s Project - Fitri, Sofia Ratna Awaliyah (Jurnal Penelitian Pendidikan Islam, 2025)
This article revisits Ismail Raji al-Faruqi’s Islamization of Knowledge as one of the most influential epistemological projects in modern Islamic thought. The study aims to examine its theoretical foundations, historical and postcolonial contexts, major scholarly debates, and contemporary relevance for Islamic education and higher education. Using a qualitative library-based method with a conceptual-critical and hermeneutical approach, the article analyzes scholarly works on Islamic epistemology, knowledge integration, educational dualism, secular modernity, and postcolonial Muslim thought. The findings show that al-Faruqi’s project should not be understood as a rejection of modern knowledge, but as an attempt to reconstruct the foundations, purposes, and ethical orientation of knowledge through tawhid, revelation, reason, empirical inquiry, and moral responsibility. However, the project remains contested due to methodological ambiguity, institutional barriers, and the risk of ideological reduction. This article argues that the Islamization of Knowledge remains relevant when reinterpreted as an ethical-epistemic framework that is plural, dialogical, interdisciplinary, and responsive to contemporary challenges such as globalization, digital transformation, and the changing landscape of Islamic higher education.